2015
DOI: 10.2147/ijn.s82061
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress by layered double hydroxide nanoparticles via an SFK-JNK and p38-NF-κB signaling pathway mediates induction of interleukin-6 and interleukin-8 in human lung epithelial cells

Abstract: Anionic nanoclays are layered double hydroxide nanoparticles (LDH-NPs) that have been shown to exhibit toxicity by inducing reactive oxidative species and a proinflammatory mediator in human lung epithelial A549 cells. However, the molecular mechanism responsible for this LDH-NP-induced toxicity and the relationship between oxidative stress and inflammatory events remains unclear. In this study, we focused on intracellular signaling pathways and transcription factors induced in response to oxidative stress cau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Likewise, it was determined that HAP NP exposure caused oxidative stress, leading to expression of antioxidant enzymes, such as catalase, superoxide dismutase (SOD), and heme oxygenase-1, via a Src family kinase (SFK)-JNK and p38-NF-κB signaling pathway in human lung epithelial A549 cells. 53 The measurement of SOD generation also showed that HAP NPs decreased the total SOD of cellular levels in C6 glioma cells. 54 Again, in an in vivo study, a dose-dependent decrease in the activity of glutathione peroxidase was observed in dermally HAP NP exposed rats.…”
Section: Discussionmentioning
confidence: 93%
“…Likewise, it was determined that HAP NP exposure caused oxidative stress, leading to expression of antioxidant enzymes, such as catalase, superoxide dismutase (SOD), and heme oxygenase-1, via a Src family kinase (SFK)-JNK and p38-NF-κB signaling pathway in human lung epithelial A549 cells. 53 The measurement of SOD generation also showed that HAP NPs decreased the total SOD of cellular levels in C6 glioma cells. 54 Again, in an in vivo study, a dose-dependent decrease in the activity of glutathione peroxidase was observed in dermally HAP NP exposed rats.…”
Section: Discussionmentioning
confidence: 93%
“…In principle, the mitochondrial electron transport chain is a major source of intracellular ROS. 74,75 Moreover, in the respiratory chain, blue light is absorbed directly by molecules, such as flavin and cytochrome oxidase, which [76][77][78][79] The process of mitochondrial redistribution with morphological changes in ARPE-19 cells under blue light irradiation has been reported previously; the mitochondria of RPE cells irradiated at a wavelength of ~ 400 nm were observed to be denatured and low level in distribution and were observed to be prominent only in the perinuclear region. 80 The same condition was reported in a similar study in which a generation of long and large mitochondria exhibited a reduction in their membrane potential for ARPE-19 cells.…”
Section: Dovepressmentioning
confidence: 67%
“…It seems that CaCO 3 nanoparticles can damage the cell membrane and consequently induce ROS, but these cytotoxic effects are not severe to affect cell prolliferation. It was reported that layered double hydroxide nanoparticles did not block cell proliferation up to 500 μg/mL, but caused ROS generation and LDH release [ 26 , 27 ]. Slightly high cytotoxicity of food nano CaCO 3 is likely to be associated with surface roughenss resulting from the grinding process of sea shells as shown in AFM images and height profile in Figure 1 B.…”
Section: Resultsmentioning
confidence: 99%